2007
DOI: 10.5551/jat.e444
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation by Hypoxia and Low-Density Lipoprotein Loading in Cultured Vascular Smooth Muscle Cells

Abstract: Aim:The aim of this study was to investigate transcriptional activation in vascular SMC cultured under hypoxic conditions and high low-density lipoprotein (LDL) levels. Methods: We cultured vascular SMC under hypoxic conditions and high LDL levels, and RNA expression profiles for more than 5800 were analyzed by DNA microarray. We performed promoter sequence analysis of genes induced by the combination of hypoxia and high LDL level conditions. Key words; Low density lipoprotein, Atherosclerosis, DNA microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The present study yielded similar results to a previous report that also examined leptin expression in HCASMCs subjected to hypoxia [ 23 ]. Under 2.5% O 2 hypoxia, significant oxidative stress induced hypoxic signaling (JNK) and activated leptin expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study yielded similar results to a previous report that also examined leptin expression in HCASMCs subjected to hypoxia [ 23 ]. Under 2.5% O 2 hypoxia, significant oxidative stress induced hypoxic signaling (JNK) and activated leptin expression.…”
Section: Discussionsupporting
confidence: 92%
“…Its expression in increased by hypoxic conditions in various tissues such as placenta, pancreas, human skin dermal fibroblasts, adipocytes, and heart [ 4 , 19 - 22 ]. In fact, leptin is the gene most induced under hypoxia in human coronary arterial smooth muscle cell (HCASMC) [ 23 ]. Functional analyses of the leptin promoter reveal that hypoxic response elements mediate transcriptional activation by hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is considered to be a specific adipocyte product. Recent reports [9,10] and our present study have shown leptin production by non-adipose cells. Leptin production by VSMCs was not widely investigated.…”
Section: Discussionmentioning
confidence: 49%
“…Leptin production by VSMCs was not widely investigated. Sugiyama et al [10] have reported that a combination of hypoxia and high low-density lipoprotein level conditions induced leptin expression in HCASMCs. Our study is the first one to investigate VSMC leptin in detail.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation